Use of alternative wood chips from new botanical species. Their impact on phenolic composition and sensory properties of a rose wine from Touriga Nacional grape variety - Santos, Filipa Ferreira Reis Cardoso dos (2018)
Mestrado em Viticultura e Enologia / Instituto Superior de Agronomia / Faculdade de Ciências. Universidade do Porto